Demetrius sacker of cities - Romm, James S. (New Haven Yale University Press, 2022)
A portrait of one of the ancient world's first political celebrities, who veered from failure to success and back again
Chapter Fourteen. "Then Don't Be a King" -- Chapter Fifteen. The Unraveling -- Chapter Sixteen. A King in Plain Clothes -- Chapter Seventeen. The Great Anabasis -- Chapter Eighteen. Twists of the Knife -- Chapter Nineteen. The Final Crossing -- Epilogue -- Chronology -- Genealogy -- Source Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- L -- M -- N -- O -- P -- R -- S -- T -- V -- W -- X -- Z
Includes bibliographical references and index
Description based on online resource; title from PDF title page (De Gruyter, viewed on December 19, 2022)
JSTOR
Keywords: Demetrius -- I, -- Poliorcetes, King of Macedonia, -- 336 B.C.-283 B.C.; Demetrius -- I, -- Poliorcetes, King of Macedonia, -- 336 B.C.-283 B.C.; Macedonia -- Kings and rulers -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Royalty; Kings and rulers; Europe -- Macedonia; Biographies